Perceived hypocrisy and deconversion in adolescents. The mediating role of irrational beliefs and identity styles - Zarzycka, Beata (Journal of beliefs and values, 2024)
Deconversion is a biographical change in which one goes from claiming adherence to a religion to departing from it. A meaning system model can help us understand the processes through which deconversion occurs. Drawing on that framework, we explored how perceiving hypocrisy in one’s religious setting influences adolescent deconversion. Irrational beliefs and identity styles of adolescents were examined as potential mediators of this relationship. In total, 369 Polish secondary school students participated in the research (65.8% female). Their mean age was 16.92 years (SD = 1.08; range = 15–19). They completed the Adolescent Deconversion Scale, Perceived Religious Hypocrisy Scale, short form of the Attitudes and Belief Scale-2, and the Identity Style Inventory. The results demonstrated that the perception of religious hypocrisy was positively related to deconversion. Moreover, the adolescents’ identity styles and propensity towards irrational beliefs partially and serially mediated the relationship between perceiving religious hypocrisy and deconverting. The results suggest that adolescents’ deconversion is related to their perception of the hypocrisy of other religious people. The theoretical and practical implications of this research are discussed.